Total flavonoids of Astragalus membranaceus protect against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced neurotoxicity in mice by inhibiting ferroptosis through SLC7A11/GPX-4 signaling pathway - Zitian Gao; Gaorui Wang; Yujie Chen; Wuke Yuan; Jun Cai; Aiping Feng; Jie Fang; Qi Xu; Xiaojun Wu (Food Science and Human Wellness)
Parkinson’s disease (PD) is a common neurodegenerative disorder with no cure. Astragalus membranaceus is used in Chinese culture as a food supplement to boost immunity. The present study aimed to explore the neuroprotective effects of total flavonoids extracted from A. membranaceus (TFA) and their protective mechanisms. TFA offered neuroprotection against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) in the mouse model of Parkinsonism, by improving behavior performance in the gait analysis and pole test, and inhibiting the decline of tyrosine hydroxylase (TH) positive neurons and TH protein expression in substantia nigra of mice. TFA also prevented 1-methyl-4-phenylpyridinium (MPP+) induced neurotoxicity in SH-SY5Y cells, by increasing GSH and GSH/GSSG ratio, and reducing reactive oxygen species. In addition, the neuroprotective effects of TFA were associated with its ability to restore MPTP/MPP+ induced downregulation of SLC7A11 and glutathione peroxidase 4 (GPX-4). In conclusion, we demonstrated that TFA exerted significant neuroprotection against MPTP/MPP+ induced neurodegeneration by inhibiting ferroptosis through the regulation of SLC7A11/GPX-4 axis, suggesting the use of TFA as a possible food supplement in the prevention of PD.